A Perspective of the Diagnosis and Management of Congenital Tuberculosis. (24th November 2016) - Saramba, Manou Irmina; Zhao, Dongchi
Abstract : Tuberculosis continues to be a prevalent disease in the world and a global public health issue in many countries. The disease is more complicated in pregnant women because it imperils unborn offspring and results in congenital tuberculosis later if undiagnosed and untreated. Congenital tuberculosis is rare entity and an uncommon disease along with a high mortality rate. Congenital tuberculosis, a severe clinical type of tuberculosis caused by Mycobacterium tuberculosis, is a serious and fatal disease if left untreated. Our study emphasizes that it is necessary and mandatory to consider congenital tuberculosis in the differential diagnosis of neonatal or pulmonary infections in infants, essentially in countries where the incidence of tuberculosis is high burden. Mother to neonatal transmission of disease is well known via transplacental transmission through the umbilical vein to the fetus, through the ingestion of infected amniotic fluid. Early detection is challenging, because of the nonspecific nature of the signs and symptoms in tuberculosis during pregnancy and infancy. The degree of clinical suspicion is the essential component of diagnosis. Furthermore, it generally has a difficult treatment and it should not be delayed while waiting for diagnostic test results. Prompt identification and proper treatment regimens for congenital tuberculosis strongly relate with enhanced outcomes.